Infrared thermography in metallic environments of WEST and ASDEX Upgrade. (March 2021) - Aumeunier, M-H.; Gerardin, J.; Talatizi, C.; Le Bohec, M.; Ben Yaala, M.; Marot, L.; Loarer, T.; Mitteau, R.; Gaspar, J.; Rigollet, F.; Courtois, X.; Houry, M.; et al.
Highlights: Infrared quantitative thermography challenging in fully reflective and radiative environment. synthetic diagnostic is a remarkable tool to reduce the risk of misleading interpretation of IR image. dedicated experiences to measure the optical properties of fusion materials. comparison of simulated and experimental data in WEST and ASDEX-U devices. Abstract: Infra-red (IR) thermography is a widely used tool in fusion devices to monitor and to protect the plasma-facing component (PFC) from excessive heat loads. However, with the use of all-metal walls in fusion devices, deriving surface temperature from IR measurements has become more challenging. In this paper, an overview of infra-red measurements in the metallic tokamaks WEST and ASDEX Upgrade (AUG) is reported and the techniques carried out in the modeling and experimental fields to deal with this radiative and fully reflective environment are presented. Experimental characterizations of metallic samples in laboratory and experiments in WEST and AUG reveal that the behavior of both the emission and the reflectance can vary significantly with surface roughness, machining process and as the plasma operation progress. In parallel, the development of a synthetic IR diagnostic has allowed for a better interpretation of the IR images by assessing the reflection patterns and their origin. This has also proven that small-scale change in the emission pattern of beveled PFC can be confused with abnormal thermal events. Numerical solutions to evaluate the contribution of the reflections associated with a variable emissivity in a fully reflective and radiative environment are finally presented.